Prognostic performance of soluble urokinase plasminogen activator receptor for 1-year mortality in Asian and Western patients with acute breathlessness. (25th November 2020) - Chew-Harris, J; Appleby, S; Kuan, W.S; Ibrahim, I; Chan, S.P; Li, Z; Liew, O.W; Frampton, C; Troughton, R.W; Chong, J.P.C; Tan, L.L; Lin, W; et al.
Abstract: Background: Soluble urokinase plasminogen activator receptor (suPAR) is a pleotropic receptor, capable of orchestrating plaque vulnerability and vascular immune dysfunction. We have previously reported on the prognostic ability of suPAR in cardiovascular disease (CVD). However the performance of suPAR to predict death in an Asian population with undifferentiated breathlessness has not been described. Methods: Patients presenting to hospital with the primary complaint of breathlessness were recruited according to identical criteria in New Zealand [(NZ), n=612] and in Singapore (n=483)]. Baseline measurements of suPAR plasma concentrations were undertaken with a CE-marked ELISA (ViroGates). NT-proBNP, hsTnT (both Roche) and standard biochemistry analytes were also measured. Statistical assessment was made using SPSS v25 (IBM), with all biomarkers treated as continuous variables and presented as median [interquartile range (IQR)]. Group comparisons were made by Mann-Whitney U test. Prognostic performance of suPAR, NT-proBNP and hsTnT for 1-yr mortality prediction was assessed using receiver operator curve (ROC) area under the curve (AUC) analysis (Z-scores) and Cox hazard regression analysis (log-values). P-value <0.05 was considered significant. Results: The adjudicated diagnosis of ADHF was more common in NZ than in Singapore (37 vs. 25%, P<0.0001) in concordance with the higher median age (16 yrs older) of NZ patients and poorer kidney function. Diabetes was however more prevalent amongst Singaporean patients. There were a total of 143 deaths [NZ, n=113 (18%); Singapore, n=30 (6%)] within 1 year from hospital admission. In both cohorts, median suPAR concentrations were higher in those who died vs those who survived (P<0.0001) (Figure). For the Singapore cohort, suPAR (AUC=0.85) discriminated 1-yr mortality better than hs-TnT (AUC=0.78) and NT-proBNP (AUC=0.79). For the NZ cohort, suPAR (AUC=0.71) was similar to hs-TnT (AUC=0.73) and NT-proBNP (AUC=0.69) for 1-yr death prediction. In the combined cohort, after the adjustment of conventional risk factors, suPAR (P=0.007) was the superior biomarker for 1-year death prediction in the subgroup of ADHF patients only (n=51/343). suPAR concentrations above a cut-off value of 3.1 ng/mL, were associated with hazard ratios of 7.4 (95% CI:1.6–17.4) (P=0.009) for Singapore patients and 2.8 (95% CI:1.5–5.3) (P=0.001) for NZ patients for death within 1 year. Conclusion: This is a first report confirming the strong prognostic ability of suPAR in mortality prediction for acutely breathless patients in an Asian population despite the presence of several demographic and clinical differences compared to a Western population. The inclusion of suPAR may add value to risk stratification models in acutely dyspnoeic patients. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Health Research Council of New Zealand, National Heart Foundation of New Zealand